Peningkatan Kemampuan Mendeskripsikan Daur Hidup Hewan Melalui Penggunaan Media Gambar Berseri Pada Siswa Tunarungu Kelas V SLB - Usman, Usman; Mustafa, Mustafa; Ningrum, Khairunnisa Justika (Universitas Negeri Makassar, 2023)
This research study focuses on the lack of ability to describe the life cycle of animals in deaf students in science subjects at SLB Negeri 1 Makassar. The method used is classroom kuantitatif aproach. The data collection method applied is a test. The subjects of this study were deaf students in class V SLB Negeri 1 Makassar with the initials MIM. This study has several conclusions, namely: 1) The ability to describe the animal life cycle of deaf students in grade V SLB Negeri 1 Makassar in Baseline 1 (A1) situations is in the very poor category. 2) The ability to describe the animal life cycle of class V deaf students in the intervention situation (B) is in the good category. 3) The ability to describe the animal life cycle of deaf students in class V at Baseline 2 (A2) is in the very good category. 4) The ability to describe the life cycle of animals using serial picture media for deaf students in class V is based on the results of analysis between situations, namely in the Baseline 1 situation (A1) very lacking, in the intervention situation (B) in the good category, and in the Baseline 2 situation (A2) ) is in the very good category.